Potent Roles of Humor in EFL Classes in Higher Education: An Exploratory Study of Lebanese Perspectives - Nadine Sami Joudi; Nawal Nabih Ayoub (European Scientific Journal, ESJ, 2023)
This paper attempts to scrutinize the attitudes and opinions of English as a Foreign Language (EFL) instructors and learners on the use of humor in higher education in Lebanon as a pedagogical tool in classroom contexts in building a harmonious relationship between instructors and students, lowering affective barriers to learning, keeping students attentive to class activities, developing creativity and increasing instructional effectiveness as well as students’ learning. It also aims to describe the instructors’ experiences in employing it in their classrooms and to determine the students’ perspectives on its potent roles in learning. In this exploratory study, a mixed-method design and a convenient sampling of participants were utilized. A total of 13 EFL instructors, working at 1 public and 4 private universities in Lebanon, and 86 EFL students participated in the study.  To describe and quantify their perceptions on the potent roles of employing humor in EFL classes, two online surveys of two sets of questions each, including closed-ended and open-ended, and four focus group discussions were administered. The overall qualitative and quantitative analysis of the data indicated that Lebanese EFL instructors and students have positive attitudes towards integrating humor as a pedagogical tool and as a fundamental part of the teaching strategies in EFL higher education classes since it creates an open communication climate, captures students’ interest in the subject matter, boosts attention, reduces anxiety, makes the instructor more approachable, and yields better instructor evaluation; however, the findings also revealed the need to train teachers to use humor artfully.